Development and Feasibility Test of a Mouth Contactless Breathing Exercise Solution Using Virtual Reality: A Randomized Crossover Trial - Jiyeon Kang; Jiwon Hong; Yean-Hwa Lee (Elsevier, 2021)
Summary: Purpose: The purpose of this study was to develop a novel mouth contactless breathing exercise solution based on virtual reality (VR), and to test its feasibility. Methods: We developed the Virtual Reality-based Breathing Exercise System (VR-BRES), a self-regulating biofeedback breathing exercise with gaming characteristics and a soft stretch sensor. The feasibility and efficacy of the VR-BRES prototype were investigated through a randomized crossover trial. Fifty healthy adults participated in the trial, and their respiratory parameters and user evaluation of the VR-BRES were compared with conventional deep breathing (CDB) exercises. Results: The respiratory parameters, forced vital capacity (Z = 4.82, 4.95, p < .001), forced expiratory volume in one second (t = 6.02, 6.26, p < .001), and peak expiratory flow (t = 5.35, 5.68, p < .001) were significantly higher during breathing exercises using the VR-BRES. User evaluation was also significantly higher for the VR-BRES in terms of efficiency (Z = 3.86, p < .001), entertainingness (Z = 5.00, p < .001), and intention to use (Z = 3.22, p = .001) compared to CDB. However, there was no difference in convenience between the two methods (Z = −0.90, p = .369). Conclusion: The VR-BRES has the potential to be an efficient breathing exercise solution. We recommend a clinical study that evaluates the effects of the VR-BRES for a certain period of time for people who need breathing exercises.